Sistema informático para la de gestión de información sobre el personal técnico de la Universidad de Granma - Casa Tumbaco, Verónica Elizabeth (2013)
In the Address of Human resources of the University of Granma it is carried out the control y prosecution of a great volume of information on the technical personnel that works in the same one. To give execution to the carried out information it is demanded the prosecution of great quantity of data y documents, what hinders the control y it favors the delay of the information. Also, the process of the information is carried out slowly, causing nuisances; with the result that the summary y analysis of these data at one time brief it is important to maintain an effective dynamics inside the business. Assisting to these necessities, software is developed to facilitate in a quick, reliable y sure way the administration of the information y prosecution of the data in the Address of Human resources in the University of Granma. The process of development of the product is carried out leaning on in free technologies y multiplatform, as NetBeans 7.2 like development environment, for the modeling of the database DB designer4, as programming language the Java 2EE with JSF, the pattern of architecture of 4 layer was implemented through the framework SPRING y HIBERNATE, as servant Apache Web Tomcat y system agent of Database MySQL.